Combination of breast imaging parameters obtained from 18F-FDG PET and CT scan can improve the prediction of breast-conserving surgery after neoadjuvant chemotherapy in luminal/HER2-negative breast cancer. Issue 113 (April 2019) - Grapin, Mathieu; Coutant, Charles; Riedinger, Jean-Marc; Ladoire, Sylvain; Brunotte, François; Cochet, Alexandre; Humbert, Olivier
Highlights: For patients with a localized luminal/HER2 negative breast cancer, 18F-FDG PET-CT may predict the probability of breast conserving surgery. Imaging data resulting from 18 F-FDG PET-CT could help clinicians and breast cancer patients to optimize clinical decision-making. The integration of imaging parameters such as total breast volume and delta metabolic tumor volume could improve the accuracy of nomograms. Abstract: Introduction: The luminal/Human Epidermal growth factor Receptor 2 (HER2) negative subtype of breast cancer has low chemo-sensitivity. When neoadjuvant chemotherapy (NAC) is indicated in this subtype, before a possible breast-conserving surgery (BCS), it is more reasonable to target tumor shrinkage than complete pathological tumor response. We aimed to identify breast and tumor 18 Fluoro-deoxy-glucose ( 18 F-FDG) PET-CT scan imaging features for the early prediction of BCS after NAC in luminal/HER2 negative subtypes of breast cancer. Material and methods: Seventy-seven consecutive women with luminal/HER2-negative breast cancer for whom BCS was initially not feasible and NAC was prescribed, to decrease tumor size before surgery, were included retrospectively. An 18 F-FDG PET-CT scan exam was performed before and after the first course of NAC. Results: After NAC, 36% (28/77) of women had a mastectomy and 64% (49/77) underwent BCS. Patients with a mastectomy had lower total breast volume (BVtotal ) (p = 0.002), lower decrease in Δmetabolic tumor volume (ΔMTV) (p = 0.03) and lower SUVmax2 (p = 0.05). Using ROC Curve analyses to define the optimal predictive threshold of BVtotal (496 cm 3 ) and ΔMTV (-17.1%), 3 subgroups of women with different odds of BCS after treatment were identified (p = 0.001): low, medium and high probability groups (respectively 29%, 62% and 82%). Conclusions: For patients with Luminal/HER2 negative breast cancer, the combination of the imaging features of the tumor and the mammary gland, obtained with 18 F-FDG PET-CT at baseline and after the first cycle of NAC, may allow the physician to evaluate the probability of BCS.